Isolation of Streptococcus species from throat swabs of school going children - K.L, Shobha; Mrs, Kusumakshi; K.M, Anand; S, Gowrish; D'Souza, Jessica; L, Ramachandra (International Journal of Pharmacology and Toxicology, 2014)
Introduction : Group A Streptococcus (Streptococcus pyogenes), is a Gram positive coccus appearing in chains and causes an incredible history of changing disease pattern. It has numerous virulence factors that helps in the adherence of the tissues, destruction of tissues and resulting in causing autoimmune complications. An attempt was made to screen for Streptococcus pyogenes throat carriers among school going children of Udupi district, Karnataka State, India. Materials and Methods: Throat swabs were collected from posterior pharynx. Swabs were immediately plated onto a sheep blood agar (Hi-Media,Mumbai,India) and transported to the laboratory within one hour of collection. The inoculated plates were incubated at 370C for 24- 48 hours in carbondioxide incubator. Organism grown on colonies were identified up to species level. Result: A total of 235 children were screened for Streptococcus pyogenes. They were in the age group of 6- 11 years. None of the children had Streptococcus pyogenes. Conclusion: Streptococcus pyogenes was not found from the throat samples in school going children More studies are required to establish an accurate value of prevalence with a larger sample size. Key words: Gram positive cocci in chains, Streptococcus pyogenes, school going children, throat swab